2017
DOI: 10.1111/jvh.12668
|View full text |Cite
|
Sign up to set email alerts
|

National treatment programme of hepatitis C in Egypt: Hepatitis C virus model of care

Abstract: Hepatitis C virus (HCV) infection is a major health problem in Egypt as the nation bears the highest prevalence rate worldwide. This necessitated establishing a novel model of care (MOC) to contain the epidemic, deliver patient care and ensure global treatment access. In this review, we describe the process of development of the Egyptian model and future strategies for sustainability. Although the magnitude of the HCV problem was known for many years, the HCV MOC only came into being in 2006 with the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 13 publications
2
142
0
Order By: Relevance
“…According to the data shown in Table 1, the median serum tacrolimus concentration of the 6 patients was 4.6 (3.3, 7.2) ng/mL, which conformed to the effective dose described in most other studies, [2][3][4][5][6] but the outcome was not the same. After analysing the basic status of these patients, we found that all 6 patients had hepatic decompensation prior to treatment with tacrolimus.…”
supporting
confidence: 75%
“…According to the data shown in Table 1, the median serum tacrolimus concentration of the 6 patients was 4.6 (3.3, 7.2) ng/mL, which conformed to the effective dose described in most other studies, [2][3][4][5][6] but the outcome was not the same. After analysing the basic status of these patients, we found that all 6 patients had hepatic decompensation prior to treatment with tacrolimus.…”
supporting
confidence: 75%
“…The national treatment strategy for control of HCV infection in Egypt39 was set by the National Committee for Control of Viral Hepatitis (NCCVH) which was established by the MoH in 2006, in response to the magnitude of the HCV problem and burden of disease in Egypt 40. This committee had an advisory board of volunteer hepatology and epidemiology professors and included international experts from Pasteur Institute, Paris, and the University of California, San Francisco.…”
Section: Treatment Strategy and Outcomementioning
confidence: 99%
“…Inspiration for such a paradigm shift could be drawn from the hugely successful hepatitis C control programme in Egypt. 10 Such a body must also be empowered to federally negotiate discounted procurements for the programme in an accountable and transparent manner. Despite the barriers to an effective strategy, there are grounds for optimism.…”
Section: The Cost Of Eliminating Hepatitis C In Pakistanmentioning
confidence: 99%